1959
DOI: 10.1177/004051755902900903
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Short Fibers in a Cotton on its Processing Efficiency and Product Quality

Abstract: The effect of the short fiber content of a cotton on yarn and fabric properties and processing efficiency, long a speculative and controversial subject, is investigated to a limited extent in this paper by the technique of cutting sliver into and ¼- and ½-in. segments and adding the resulting short fibers to the parent cotton. The results indicate that increases in short fibers are detrimental to virtually all yarn and fabric properties and require increased roving twist for efficient drafting during spinning.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0

Year Published

1961
1961
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 6 publications
3
7
0
Order By: Relevance
“…It is thought that the apparent deterioration in the spinning efhciency of American cotton in recent years may be put into proper perspective if these considerations are taken into account. Summary and Conclusions 1'ilot-scale spinning on standard equipment corroborated and reinforced the findings of earlier work of this series [7,8,9] ; namely, that increases in short fiber content result in ( 1 ) decreased yam strength, with decreases in excess of 1 ~~~ in tenacity for each 1~ increase in short fibers ; (2) decreased yarn elongation; ( 3 ) decreased yan1 appearance grade and evenness; (4) increased difficulty in spinning at medium yarn numbers and low twists; and The present study threw further light on the interplay of short fiber content and the twist required for maximum strength. In the cottons studied it was found that the short fiber content appeared to have no influence on the twist required for maximum skein tenacity in coarse and medium size yarns.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…It is thought that the apparent deterioration in the spinning efhciency of American cotton in recent years may be put into proper perspective if these considerations are taken into account. Summary and Conclusions 1'ilot-scale spinning on standard equipment corroborated and reinforced the findings of earlier work of this series [7,8,9] ; namely, that increases in short fiber content result in ( 1 ) decreased yam strength, with decreases in excess of 1 ~~~ in tenacity for each 1~ increase in short fibers ; (2) decreased yarn elongation; ( 3 ) decreased yan1 appearance grade and evenness; (4) increased difficulty in spinning at medium yarn numbers and low twists; and The present study threw further light on the interplay of short fiber content and the twist required for maximum strength. In the cottons studied it was found that the short fiber content appeared to have no influence on the twist required for maximum skein tenacity in coarse and medium size yarns.…”
Section: Introductionsupporting
confidence: 82%
“…In the cottons studied it was found that the short fiber content appeared to have no influence on the twist required for maximum skein tenacity in coarse and medium size yarns. This conclusion has been reported before (7,8]. However, there were indications that short fiber content may affect the twist necessary for maximum strength in the finer yarn sizes, and further investigation is needed.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…has heen published elsewhere [1], and a manuscript covering the principal fin<lings is in preparation. 3. While it is admitted that silglltl%l contradictory data on the effect of short fibers on the twist required for maximum strength of fine yarns have been found.…”
mentioning
confidence: 99%